Analysis of Scabies Factors among Male and Female Students at the Islamic Boarding School in the East Jakarta Region in 2022 - Ago Harlim; Marcella Scofany Theresia Turot; Mohammad Zen Rahfiludin; Kelvin (JURNAL KESEHATAN LINGKUNGAN, 2026)
Introduction: Scabies, also known as ‘gudik’ in Indonesian, is a disease accounted by the itch mite Sarcoptes scabies var. hominis that is commonly transmitted through fomites including shared use of beddings, clothings, soap, towels, and many household items. This parasitic disease is typically identified through four main cardinal signs including nocturnal itching, a shared complaint among a larger group, finding burrows on the skin, and the presence of mites in skin scrapings. This study aims to identify the factors associated with scabies in a boarding school in East Jakarta, a densely populated area at risk of such parasitic infestation. Methods: This study is an analytical descriptive study aimed to identify factors related to scabies, including lighting, water cleanliness, bed hygiene, cleanliness of clothing and prayer equipment, towel hygiene, use of soaps or antiseptics, and nutritional needs. Questionnaires, physical examinations, and laboratorium parameters were utilized appropriately as data in this study. Results and Discussion: The findings identified a correlation between lighting, water hygiene, cleanliness of clothing and prayer items, towel hygiene, and the use of soap or antiseptics with scabies occurrence. However, no significant correlation was found between bed hygiene or nutritional factors and scabies in the boarding school. Conclusion: Low sunlight exposure, poor water hygiene, unclean clothing or prayer items, inadequate towel hygiene, and lack of antiseptic soap use increased the scabies occurrence at Nurul Hijrah Islamic Boarding School. The most influential factor associated with scabies occurrence was sunlight exposure.